2008
DOI: 10.1088/0031-9155/53/13/008
|View full text |Cite
|
Sign up to set email alerts
|

Reference dosimetry in a scanned pulsed proton beam using ionisation chambers and a Faraday cup

Abstract: In order to give the correct dose to a patient, the monitor chamber for a proton scanning system has to be calibrated. As recombination of ion pairs occurs in the monitor chamber, the relation between the number of particles traversing it per time unit and the ionization chamber signal is not linear. A method developed for a scanned pulsed proton beam taking the nonlinear monitor signal into account is described. A vital part of the reference dosimetry procedure is to determine the absorbed dose under referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 19 publications
2
47
0
Order By: Relevance
“…For the beam to be pulsed or pulsed‐scanned, t beam must be short compared to t IC and the time between pulses must be long compared to t IC . Other possible intermediate conditions have been described by Lorin et al . The Proteus‐235 beam pulses consist of 0.8 ns micro‐pulses separated by 10 ns intervals.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…For the beam to be pulsed or pulsed‐scanned, t beam must be short compared to t IC and the time between pulses must be long compared to t IC . Other possible intermediate conditions have been described by Lorin et al . The Proteus‐235 beam pulses consist of 0.8 ns micro‐pulses separated by 10 ns intervals.…”
Section: Methodsmentioning
confidence: 87%
“…concluded that for proton beams used for treating ocular targets (usually operating at high dose rates), the recombination correction factor can be overestimated by up to 2% if the recommendation from TRS‐398 is followed without consideration. Lorin et al . showed that the signal from a thimble chamber should be corrected when evaluating a scanning proton beam.…”
Section: Introductionmentioning
confidence: 99%
“…Proton therapy and ion therapy centers might have, in the future, access to clinical dedicated calorimeters to determine the absorbed dose‐to‐water to avoid additional uncertainty on the ion chamber charge measurement (e.g., due to large ion recombination effects). Dedicated calorimeters would also avoid the need to determine beam quality correction factors.…”
Section: Resultsmentioning
confidence: 99%
“…This approach, based on absolute dose per MU, is equivalent to the approach based on absolute dose per particle used at other institutions. 4,23 …”
Section: Iic Conversion Of Mc-generated Iddsmentioning
confidence: 99%